Beneficial Effects of a Short Course of Physical Prehabilitation on Neurophysiological Functioning and Neurovascular Biomarkers in Patients Undergoing Coronary Artery Bypass Grafting - Trubnikova, Olga A.; Tarasova, Irina V.; Moskin, Evgeniy G.; Kupriyanova, Darya S.; Argunova, Yuliya A.; Pomeshkina, Svetlana A.; Gruzdeva, Olga V.; Barbarash, Olga L. (Frontiers in Aging Neuroscience, 2021)
This study aimed to evaluate the effects of a short course of physical prehabilitation on neurophysiological functioning and markers of the neurovascular unit in patients undergoing coronary artery bypass grafting (CABG). We performed a prospective randomized study involving 97 male CABG patients aged 45–70 years, 47 of whom underwent a 5–7-day preoperative course of aerobic physical training (PhT). Both groups of patients were comparable with respect to baseline clinical and anamnestic characteristics. An extended neuropsychological and electroencephalographic (EEG) study was performed before surgery and at 7–10 days after CABG. Markers of the neurovascular unit (S100β, NSE, and BDNF) were examined as metabolic correlations of early postoperative cognitive dysfunction (POCD) at three time points: before surgery, within the first 24 hours after surgery, and 7–10 days after CABG. POCD developed in 58% of patients who underwent preoperative PhT, and in 79.5% of patients who did not undergo training, 7–10 days after CABG. Patients without prehabilitation demonstrated a higher percentage of theta1 power increase in the relative change values as compared to the PhT patients (p=0.015). The short preoperative course of PhT was associated with low plasma S100β concentration, but high BDNF levels in the postoperative period. Patients who underwent a short preoperative course of PhT had better cognitive and electrical cortical activity indicators. Markers of the neurovascular unit indicated lower perioperative brain injury after CABG in those who underwent training. A short course of PhT before CABG can decrease the brain’s susceptibility to ischemia and reduce the severity of cognitive impairments in cardiac surgery patients. Electrical brain activity indicators and neurovascular markers, such as S100β and BDNF, can be informative for the effectiveness of cardiac rehabilitation programs.